Multi-objective optimization controller placement problem in internet-oriented software defined network - Zhang, Bang; Wang, Xingwei; Huang, Min (Computer communications, 2018)
In Internet-oriented Software Defined Network (SDN), the feasibility and scalability are guaranteed by the cooperation among multiple controllers, thus the effective placement of these controllers becomes the significant task. In this paper, we formulate a Multi-objective Optimization Controller Placement (MOCP) problem, which focuses on achieving high network reliability, load balance among controllers, and low latency among controllers and switches. The MOCP covers three specific questions: where the controllers should be placed, how to assign controllers to switches, and how many routing requests should be processed by each controller. We use Adaptive Bacterial Foraging Optimization (ABFO) algorithm and redefine its computation rules to solve the MOCP problem. Simulation results demonstrate that the proposed ABFO based MOCP scheme is effective and has better performance than the existing ones.